Ophiorrhiza hoanglienensis (Rubiaceae), a new species from north-western Vietnam - Nguyen, Thanh Trung; Wei, Yi-Gang; Wen, Fang; Le, Khuong Duy; Do, Truong Van (Phytotaxa, 2020)
Ophiorrhiza hoanglienensis, a new species from Hoang Lien mountain range, north-western Vietnam, is described and illustrated. The new species is characterized by oblong-lanceolate stipules, equal or subequal paired leaves, congested-cymose inflorescences with 5–10-flowered, distylous flowers, well-developed bracts, lanceolate, 15–20 mm long, unequally 5-lobed calyx with narrowly lanceolate lobes, longest one 3.2–3.5 mm long, shortest one 1.2–2 mm long, exclusively white corolla with 25–28 mm long tube and ovate to broadly triangular lobes, dorsally ribbed without horn. The information on ecology, conservation status, and comparison with similar species is also provided.